2010
DOI: 10.5021/ad.2010.22.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Usefulness of the Serum-Specific IgE, the Skin Prick Test and the Atopy Patch Test Compared with That of the Oral Food Challenge Test

Abstract: Background: Atopic dermatitis (AD) is frequently associated with food allergies. In addition to the skin prick test (SPT) and serum-specific IgE, the atopy patch test (APT) has been introduced as a diagnostic procedure for food allergies. Objective: Our aim was to evaluate the diagnostic value of the APT, the SPT and the serum-specific IgE levels compared with that of oral food challenge test against milk and egg in AD patients. Methods: We conducted the SPT and APT, and determined the serum-specific IgE level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
6
11
0
6
Order By: Relevance
“…There were conflicting results in the previous literature regarding the use of APT for the diagnosis of food allergies (Table 5). In agreement with previous studies (8)(9)(10)(11)(12)(19)(20)(21)(22)(23), we found that sensitivity to egg and cow's milk was low. On the other hand, our results showed remarkably lower specificity (73%) for APT in comparison with the previous studies (8,9,11,19,20,23).…”
Section: Discussionsupporting
confidence: 93%
“…There were conflicting results in the previous literature regarding the use of APT for the diagnosis of food allergies (Table 5). In agreement with previous studies (8)(9)(10)(11)(12)(19)(20)(21)(22)(23), we found that sensitivity to egg and cow's milk was low. On the other hand, our results showed remarkably lower specificity (73%) for APT in comparison with the previous studies (8,9,11,19,20,23).…”
Section: Discussionsupporting
confidence: 93%
“…After reviewing the full‐text, 40 articles were removed including 4 studies of which we were unable to find the full‐text. Finally, of the remaining 45 candidate articles, 4 studies were removed because the data we calculated based on the provided data were inconsistent with the information mentioned in the articles. We contacted the authors and no response was received.…”
Section: Resultsmentioning
confidence: 99%
“…For example, SPT is not practical in patients who have extensive eczema, dermographism, urticaria, or who are taking antihistamines or other medications which interfere with the proper interpretation of the test results (Table 2). In vitro test methods may be less sensitive [11,12] and/or less specific [13,14] than SPT depending on the method utilized and the allergens employed. Furthermore, in subjects with very high total serum IgE antibodies, low levels of specific IgE antibodies of doubtful clinical relevance are often detected.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%